Serological Profiles of Systemic Lupus Erythematosus in Humanized Mice and Pristane-Induced Lupus Models - Chilmi, Syahrul; Airlangga, Dimas Ikhsan; Susianti, Hani; Handono, Kusworini (Folia Medica Indonesiana, 2024)
Highlights: 1. This study compared the serological markers of pristane-induced mice to humanized mouse models of lupus achieved by transplanting stem cells from lupus patients, which is a novel method in Indonesia. 2. This study will allow for more accurate research into the pathophysiology of the disease and the development of new lupus treatment strategies. Abstract More studies related to systemic lupus erythematosus (SLE) therapy are urgently needed because of the current insufficiency in treatment effectiveness. However, due to ethical limitations, researchers use experimental animals as a substitute for conducting studies on humans. Models commonly used to study lupus include the pristane-induced mouse model and the recently developed humanized mouse model. The second model involves implanting human immune cells into immunodeficient mice. This study compared the serologic profiles of lupus antibodies, the antinuclear antibodies (ANA) and anti-double stranded DNA (anti-dsDNA), in both mouse models. The aim was to determine which one is more promising for use as a lupus animal model. Thirty BALB/c mice (Mus musculus) were used as subjects and divided into three groups: K1, K2, and K3. K1 served as the control group, consisting of healthy mice that received a placebo. The K2 mice were intraperitoneally injected with 0.5 cc of pristane. The K3 mice were transplanted with stem cell cultures from SLE patients, resulting in humanized mice with immune deficiencies. The mice were observed for 16 weeks, during which the ANA and anti-dsDNA levels in their serum were obtained for analysis using the Kruskal-Wallis test (p<0.05). The comparison revealed differences in the average ANA and anti-dsDNA levels among the three groups. K3 had the highest ANA and anti-dsDNA levels, followed by K1 and K2. The Kruskal-Wallis test indicated that the differences were not significant in the mean levels of ANA (p=0.156) and anti-dsDNA (p=0.061). In conclusion, the humanized mouse model has higher ANA and anti-dsDNA antibody levels compared to the pristane-induced mouse model, albeit without a significant difference. This suggests a positive picture of the humanized mouse model of lupus, making it an invaluable tool for studying the disease and testing potential therapeutic interventions.